UPAYA MENINGKATAN KEMAMAPUAN MOTORIK HALUS ANAK MELALUI KEGIATAN MELIPAT KERTAS PADA SISWA USIA 5-6 TAHUN (TK B) DI TKIT QURROTA A'YUN – BONTANG -KALTIM - Lutfiyah; Arbayah; Sjamsir, Hasbi (BEduManagers Journal : Borneo Educational Management and Research Journal, 2022)
The formulation of this class action research problem is whether toilet training activities can increase the independence of children aged 5-6 years in group B at TKIT Qurrota A'yun Bontang Selatan for the 2021-2022 school year? The type of research used is classroom action research. The cycle in this study was carried out 2 cycles and each cycle five meetings. The subjects in this study were group B totaling 15 children, consisting of 9 boys and 6 girls. Data collection techniques are carried out with worksheets and observations, while data analysis techniques use average assessments, assessments for learning completeness and individual learning completeness. The results of this study showed that through folding activities can improve the fine motor skills of group B students at TKIT Qurrota A'yun Bontang. Improving students' abilities is said to be successful if the percentage of children's independence reaches 75%